Secondary Market Liquidity and Security Design: Theory and Evidence from ABS Markets - Friewald, Nils; Hennessy, Christopher A.; Jankowitsch, Rainer (Review of Financial Studies, 2016)
We develop and empirically test a theory of optimal security design under adverse selection accounting for strategic trading by uninformed investors who will liquidate a security in secondary markets only if their idiosyncratic carrying costs exceed the security's expected trading loss. Such investors demand primary market discounts equaling expected carrying costs borne plus trading losses incurred. Issuers minimize the total illiquidity discount by splitting cash-flow into tranched debt claims with liquidity predicted to increase with seniority, while the optimal number of tranches increases with underlying cash-flow risk. Empirical tests confirm our model predictions. Received November 7, 2013; accepted November 14, 2015 by Editor Itay Goldstein.